Preventive and repressive strategies to limit the number of commercial robberies in Denmark - Kruize, Peter (Journal of Scandinavian studies in criminology and crime prevention, 2001)
In this article, the impact of preventive and repressive measures to limit the number of commercial robberies is evaluated. This is done by analysing national statistics, register data, police documents and interview material of inmates convicted for commercial robbery. Preventive measures are met by counterstrategies. The effect of the introduction of paint cartridges - after detonation the bills are rendered unusable because of paint damage - is documented. The effect is, however, not a longlasting one. Arrest is a crucial marker in the decision to continue or to desist from commercial robbery. The arrest rate is high. Most convicted commercial robbers have a tendency to continue with crime after arrest and completion of sentence, but only a few continue with commercial robbery. The empirical data do not allow for a definitive conclusion on whether it is the offender's perception of the probability of future arrests, or of the severity of their outcomes that is responsible for desisting from commercial robbery. Both factors presumably influence this decision, but perceptions concerning the likelihood of arrest are likely to be more important